2012
DOI: 10.1007/s11434-012-5385-7
|View full text |Cite
|
Sign up to set email alerts
|

Relation between mineral composition of human hair and common illnesses

Abstract: The aim of the present study was to find the relation between mineral composition of human hair and illnesses such as infections of the respiratory system, asthma, vertigo, migraine, nervousness, hair loss, dandruff, brittle fingernails and white spots on fingernails. The mineral content of human hair was determined by multielemental analysis using ICP-OES and ICP-MS. Information about the health condition of the examined subjects was obtained by questionnaire. It was found that the hair of individuals who cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…In accordance with other authors [ 55 , 85 , 102 , 116 ], also Ni, considered a carcinogen [ 117 ] and responsible for the most common type of allergy [ 16 ], was found in higher concentrations in the hair of females than males. However, our results are in contrast with the data obtained by Barbieri et al [ 113 ] and Peña-Fernández et al [ 50 ], who showed that the hair of males contained more Ni than females (females = 0.23 ± 4.89 mg kg −1 vs. males = 0.3 ± 6.5 mg kg −1 ; and females = 0.38 ± 0.34 mg kg −1 vs. males = 0.58 ± 0.34 mg kg −1 , respectively).…”
Section: Resultssupporting
confidence: 89%
“…In accordance with other authors [ 55 , 85 , 102 , 116 ], also Ni, considered a carcinogen [ 117 ] and responsible for the most common type of allergy [ 16 ], was found in higher concentrations in the hair of females than males. However, our results are in contrast with the data obtained by Barbieri et al [ 113 ] and Peña-Fernández et al [ 50 ], who showed that the hair of males contained more Ni than females (females = 0.23 ± 4.89 mg kg −1 vs. males = 0.3 ± 6.5 mg kg −1 ; and females = 0.38 ± 0.34 mg kg −1 vs. males = 0.58 ± 0.34 mg kg −1 , respectively).…”
Section: Resultssupporting
confidence: 89%
“…Generally, Zn and Cu are harmful if consumed in large quantities. For example, increased level of Cu can be found in the hair of hair loss patients [40]. Mean Zn concentration of cook group at Lhasa was higher than those of other areas [23,[41][42][43], probably due to high Zn exposure within kitchen (0.25 μg/m 3 , [36]).…”
Section: Comparisons With Other Regionsmentioning
confidence: 99%